Omnibus Law In The Dynamics Of Constitutional Law: A Comparative Research Of Indonesia, The United States, The Philippines, And Canada - Kaharuddin Kaharuddin; Dinar Karunia; Oemar Moechthar; Ave Maria Frisa Katherina (Fakultas Hukum Universitas Lampung, 2025)
The omnibus law is a legislative technique designed to streamline regulations by consolidating diverse legal norms into a single statute. In Indonesia, this method has been adopted through the Job Creation Law to enhance legislative efficiency and stimulate economic growth. However, its implementation has raised concerns regarding constitutional democracy, public participation, and adherence to the rule of law as articulated in the 1945 Constitution. This article explores the tension between regulatory efficiency and democratic principles within Indonesia’s constitutional framework. Key issues include limited public engagement, potential infringements of constitutional rights, and the erosion of checks and balances in the legislative process. Using a normative and comparative approach, the research concludes that while the omnibus law offers potential for regulatory reform, its application must be grounded in democratic values, transparency, and social justice to uphold the rule of law.